Importance of Pseudo-cereals in Human Health - Kumari, Megha; Singh, Teekam; Devi, Ayekpam Dollina (Chronicle of Bioresource Management, 2022)
Pseudo-cereals, including amaranth, quinoa, and buckwheat, have gained increasing recognition for their exceptional nutritional value and health benefits. Unlike traditional cereals, they are rich in high-quality proteins containing essential amino acids, dietary fiber, vitamins, and minerals such as phosphorus, potassium, and magnesium. Their gluten-free nature makes them an excellent dietary option for individuals with gluten intolerance or celiac disease. Regularly consuming pseudo-cereals has been associated with improved heart health, blood sugar regulation, enhanced digestion, and stronger immunity. Additionally, they contribute to weight management due to their high fiber content and satiety effects. Pseudo-cereals play a crucial role in promoting sustainable agriculture and food security. Their versatility in culinary applications and growing demand in the health food market further emphasize their significance in modern diets.